ANTITHROMBIC COMPOSITE MATERIAL - MIYAZAKI TAKESHI; YASHIMA EIJI; MIYAUCHI TOKUYUKI; MURATA TAKASHIGE; MARUYAMA YUKIRO; AKASHI MITSURU (1989)
PURPOSE:To obtain a prostacyclin deposited hydrogel-contg. high polymer so that an antithrombic composite material can be obtd. by constituting the material of the high-polymer material dispersed with the hydrogel contg. the prostacyclin. CONSTITUTION:The production of the hydrogel is executed by a method of adding a water soluble monomer and water soluble functional monomer to an aq. soln. contg., for example, a redox polymn. initiator, etc., and the prostacyclin and effecting radical polymn. under ice cooling to synthesize the hydrogel. The fine particles of the synthesized dry hydrogel contg. the prostacyclin are dispersed in the high-polymer material such as polyvinyl chloride, segmented polyurethane or polyurethane/polydimethyl siloxane copolymer having the properties as the medical material by a mechanical working method such as kneading or the above-mentioned material is dissolved in a suitable org. solvent to prepare a high-polymer soln. of a high concn. The synthesized hydrogel pulverized to fine particles is dispersed therein and is then subjected to solvent removal to immobilize the prostacyclin. The antithrombic composite material is thus obtd.